The interaction between a keystone plant species and its dominant epiphyte on Marion Island : climate change implications - Buwa, Ziphokazi Siyasanga (Stellenbosch : Stellenbosch University, 2011)
Thesis (MSc)--University of Stellenbosch, 2007.